Coenzyme Q10 and/or Vitamin E Supplementation for Polycystic Ovarian Syndrome - Irianto, Christian Bobby; Prasetyadi, Erick Giovanni (PT. Kalbe Farma Tbk., 2021)
Excessive androgens, insulin resistance, and changing estrogen levels in polycystic ovarian syndrome (PCOS) could affect the metabolic markers and lead to the increment of oxidative stress level. Coenzyme Q10 (CoQ10) is an organic molecule ubiquitously present in cell membranes and mitochondria. It is known to inhibit the peroxidation of cell membrane lipids and reduce the oxidation of circulating lipids, decreasing oxidative stress-induced cell damage. Vitamin E, an exogenous lipid-soluble molecule with antioxidant property, is a direct free radical scavenger that protects the cell membrane from lipid peroxidation and activates intracellular antioxidant enzymes. Some studies suggest that the co-supplementation of CoQ10 and vitamin E has strong synergistic outcomes in women with PCOS. The combination of those antioxidant agents is more likely to have better reproductive and metabolic outcomes.Â Kadar androgen berlebih, resistensi insulin, dan perubahan kadar estrogen pada sindrom ovarium polikistik (SOPK) dapat memengaruhi parameter metabolik dan meningkatkan kadar stres oksidatif. Koenzim Q10 (CoQ10) merupakan molekul organik yang banyak ditemukan di dalam membran sel dan mitokondria. Molekul tersebut diketahui dapat menghambat proses peroksidasi lipid membran sel dan mengurangi proses oksidasi lipid dalam sirkulasi, sehingga berdampak mengurangi kerusakan sel yang disebabkan oleh reaksi stres oksidatif. Vitamin E yang merupakan molekul eksogen larut lemak berperan melindungi membran sel dari proses peroksidasi lipid dan membantu aktivasi enzim antioksidan intraseluler. Beberapa penelitian menunjukkan bahwa ko-suplementasi CoQ10 dan vitamin E memberikan dampak signifikan pada wanita dengan SOPK. Kombinasi dua antioksidan tersebut memberikan efek lebih baik dibandingkan pemberian terpisah.